Anti-patterns in knowledge management. (2015) - Israilidis, John; Lock, Russell; Cooke, Louise
Particularly in multinational organisations, knowledge management initiatives often fail to deliver cost-effective solutions, support knowledge transfer mechanisms, and measure up to expectations. This paper identifies dysfunctional KM scenarios and formally describes necessary actions to resolve such issues by definition of the concept of KM anti-patterns. The work is aimed primarily at practitioners, i.e., managers and senior executives, in order to enable fast and effective problem identification and resolution, as well as cut costs for managing knowledge due to dysfunctional, inefficient or otherwise inappropriate KM practices.